Pengaruh Pembelajaran Menggunakan Model Project Based Learning berbantu Padlet terhadap Keterampilan Berpikir Kreatif Siswa - Rizka Nurwati Yanuar; Idad Suhada; Sri Maryanti (Edu Berkah Khatulistiwa, 2023)
Students' creative thinking skills are one of the skills that students must have in the 21st century. Students' creative thinking skills can be measured through the results of tests given to students. The research aims to describe the effect of learning using the padlet-assisted project-based learning model on students' creative thinking on kingdom Plantae material. This experimental research uses a non-equivalent control group design. The population in this study was all class X SMA in one of the schools in the Bandung district. The research sample used two classes with quasi-experimental methods and purposive sampling techniques. The research instrument consisted of observation sheets and essay test questions which included indicators of students' creative thinking with analysis of prerequisite test data and hypothesis testing. The results of the research conducted using the independent sample t-test obtained a tcount value of 0.001 <0.05 indicating that there was a positive influence on the use of the padlet-assisted project-based learning model on students' creative thinking skills.